AGROSANOATE OF MAJILARIDE ELECTRICITY IS ANALYZED IN REAL TIME (World Bulletin of Public Health, 2024)
This article analyzes the operating conditions and causes of failure of electrical equipment. It has been shown that the assessment of the technical condition of agricultural electrical equipment, their effective use and increasing their reliability is the main factor for increasing production efficiency.
Keywords: agriculture; technological process; electric motor; failure